2006
DOI: 10.1007/s10725-005-5088-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Growth Regulators on Quality Parameters and Ginsenosides Accumulation in Panax quinquefolium L. Roots

Abstract: American ginseng (Panax quinquefolium L.) is a perennial medicinal herb originally grown in Canada and USA, and recently also in China, Australia, Holland and Poland. Several commercial preparations are produced from ginseng roots, that are known for their antifatigue, antitumor, antistress and immune system stimulating functions. The medicinal properties are due mainly to the active components -ginsenosides. In this work, the results of field cultivation experiments are presented that examine the effects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Choi et al (2007), while studying the chemical characteristics of the field and mountain-cultivated ginseng roots, recorded 6.80 and 7.24 mg/g Rb1 in five-year-old roots, respectively, which was similar to the content recorded in our study. These results were in line with the studies of Kołodziej et al (2006) and Ahn et al (2013) while studying the accumulation of ginsenosides in ginseng roots. Similarly, Dai et al (2020) also recorded various ginsenosides like Rb1, Rb2, Rg1, and Rg2 in the same range as recorded in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Choi et al (2007), while studying the chemical characteristics of the field and mountain-cultivated ginseng roots, recorded 6.80 and 7.24 mg/g Rb1 in five-year-old roots, respectively, which was similar to the content recorded in our study. These results were in line with the studies of Kołodziej et al (2006) and Ahn et al (2013) while studying the accumulation of ginsenosides in ginseng roots. Similarly, Dai et al (2020) also recorded various ginsenosides like Rb1, Rb2, Rg1, and Rg2 in the same range as recorded in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The height of P. wangianus, P. japonicus and P. vietnamensis aerial shoots showed a similar pattern in growth relative to the plant age (Shu 2007). Kołodziej et al (2006) reported that there were three to five leaflets in P. quinquefolium two-year-old plant, 10 leaflets from three to six years which keep on increasing and reached 20 leaflets in 10-to 11-year-old plants. These growth trends are as per the studies of Guo et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Current production of CPTs relies on their extraction from intact plants of different species. Root culture in vitro (adventitious or transformed) is reported to have a remarkable ability to produce plant secondary metabolites (Barbara et al 2006;Wadegaonkar et al 2006;Wu et al 2007;Putalun et al 2007;Verma et al 2007). Rapid propagation of the plants as well as the induction of transformed/ untransformed roots in vitro is the most feasible strategy for removing the stress on the natural population.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside content is affected by water stress (Lim et al, 2006;Mudge, 2013), light (Foumier et al, 2003;Yu et al, 2005), mineral content (Li and Mazza, 1999), and temperature (Jochum et al, 2007). It is also affected by biotic factors such as plant growth regulators, plant age, and genotype (Court et al, 1996;Lim et al, 2005;Barbara et al, 2006;Um et al, 2017).…”
Section: Introductionmentioning
confidence: 99%